Pottery from the workshop of sextus metilius maximus (Crikvenica-igralište/Ad Turres, northern Dalmatia) - Ožanić Roguljić, Ivana (Rei Cretariae Romanae Fautorum Acta, 2012)
A Roman ceramic workshop was found in Crikvenica (Ad Turres, Croatia) at a site called “igralište”. During the excavations from 2004 to 2010 at Crikvenica-igralište four kilns were found and completely excavated. By the stamps on the bricks we know that the workshop was owned and managed by Sextus metilius maximus. the workshop operated from the second half of the 1st century BC until the end of the 2nd century aD and produced ceramic construction material, amphorae and other types of pottery. Chemical analysis has shown that the clay used for making the objects is from the site. Several products of the workshop have been presented through literature, congresses and lectures i.e. flat-bottomed adriatic amphorae of the Crikvenica type, stamped bricks and thin walled pottery (Lipovac vrkLjan 2007: 26; Lipovac vrkLjan/Lugović 2008, 34–36; Lipovac vrkLjan 2009, 309–315).